Low‐Temperature Atomic Layer Deposition of MoS2 Films. (7th April 2017) - Jurca, Titel; Moody, Michael J.; Henning, Alex; Emery, Jonathan D.; Wang, Binghao; Tan, Jeffrey M.; Lohr, Tracy L.; Lauhon, Lincoln J.; Marks, Tobin J.
Abstract: Wet chemical screening reveals the very high reactivity of Mo(NMe2 )4 with H2 S for the low‐temperature synthesis of MoS2 . This observation motivated an investigation of Mo(NMe2 )4 as a volatile precursor for the atomic layer deposition (ALD) of MoS2 thin films. Herein we report that Mo(NMe2 )4 enables MoS2 film growth at record low temperatures—as low as 60 °C. The as‐deposited films are amorphous but can be readily crystallized by annealing. Importantly, the low ALD growth temperature is compatible with photolithographic and lift‐off patterning for the straightforward fabrication of diverse device structures.